ANALISIS JANGKAUAN SINYAL HANDPHONE DAN OPTIMASI PENEMPATAN BTS (BASE TRANSCEIVER STATION) DI KECAMATAN MAPAT TUNGGUL SELATAN KABUPATEN PASAMAN - Fitri Dayanti; Triyatno Triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
The research of aims are :1) know the influence of the BTS distance to the receiver of the signal, the height ot the place, and the direction of slope to strength of cell phone signal in the Kecamatan Mapat Tunggul Selatan. 2) know the suitability of BTS (Base Transceiver Station) towers in the Kecamatan Mapat Tunggul Selatan. This research is quantitative with a spatial approach by looking at the strength of the signal with the physical condition of the region and seeing the influence of signal strength with BTS specifications, namely the distance from BTS, the height of the place and the direction of the slope. Using linear regression analysis and overlays.The results of this research are: 1)The height of the place is significant value of 0,011 there is enough evidence to say that the height variable effects the signal strength, trust level of 0,05. Distance from BTS significant value of 0,000 enough evidence to state the variable distance from BTS has an effect on signal, trust level of 0,05. The direction of the slope is significant 0,258 not enough evidence that the direction of the slope variable influences the signal strength, trust level of 0,05. 2) The results of the overlay of the slope class map, settlement and the height of the place shows that building a BTS tower in Kenagarian Muaro Sungai Lolo is not suitable due to the distance of the population apart, to the number of adjacent population does not reach 1.000 families. Seen from the geographical situation the area is very difficult to build a BTS tower, so that the Kecamatan Mapat Tunggul Selatan can not build a BTS tower in 2019.